Penerapan Total Productive Maintenance (TPM) pada Mesin Press Sinohara 60 T Menggunakan Metode Overall Equipment Effectiveness (OEE) - Alfisyahr, Nurfadia; Hapid Maksum, Apid; Wahyudin, Wahyudin (Industrika : Jurnal Ilmiah Teknik Industri, 2025)
PT Ciptaunggul Karya Abadi is a company engaged in manufacturing of metal stamping parts, tools and dies. At PT Ciptaunggul Karya Abadi, the machine that is often used is a press machine. The 60 T press is a machine that often experiences breakdowns among other types of machines. The absence of routine maintenance checksheet filling is one of the foundations for the need to analyze the application of Total Productive Maintenance to assess machine productivity and effectiveness so as to minimize the occurrence of defects and large losses. Measurement of machine effectiveness at the company can be done with the Total Productive Maintenance (OEE) method. The Total Productive Maintenance method is defined as a measure of total equipment performance, namely the extent to which the equipment does what it is supposed to do. This method is used in measuring the effectiveness of the use of an equipment or system by including several points of view in the calculation process. The calculation results obtained that the average Availability Rate is 94%, the Performance Rate is 90% and the Quality Rate is 97%. It can be concluded that the Performance Rate value of the 60 T sinohara press machine at PT Ciptaunggul karya Abadi does not meet the world class OEE standard. The six big losses factors can be considered as common factors that cause ineffectiveness. Keywords: Maintenance, OEE, Total Productive Maintenance (TPM)